2016
DOI: 10.1249/mss.0000000000000789
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Characteristics and Substrate Energetics in Lifelong Endurance Athletes

Abstract: Purpose The goal of this study was to explore the effect of lifelong aerobic exercise (i.e. chronic training) on skeletal muscle substrate stores (intramyocellular triglyceride [IMTG] and glycogen), skeletal muscle phenotypes, and oxidative capacity (ox), in older endurance-trained master athletes (OA) compared to non-competitive recreational younger (YA) athletes matched by frequency and mode of training. Methods Thirteen OA (64.8±4.9 yo) exercising ≥ 5 times/week were compared to 14 YA (27.8±4.9 yo) males … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 44 publications
6
31
1
Order By: Relevance
“…Chronic exercise in older men and women maintains high insulin sensitivity (Amati et al 2009;Amati et al 2012) similar to that of young endurance-trained athletes (Dube et al 2016). Together, these findings strongly support the idea that age per se is not the cause of skeletal muscle metabolic impairments, and that chronic exercise is a primary determinant of insulin sensitivity.…”
Section: Insulin Sensitivitysupporting
confidence: 56%
“…Chronic exercise in older men and women maintains high insulin sensitivity (Amati et al 2009;Amati et al 2012) similar to that of young endurance-trained athletes (Dube et al 2016). Together, these findings strongly support the idea that age per se is not the cause of skeletal muscle metabolic impairments, and that chronic exercise is a primary determinant of insulin sensitivity.…”
Section: Insulin Sensitivitysupporting
confidence: 56%
“…A total of 12 studies (Carrick-Ranson et al, 2014a;DubÉ et al, 2016;Hawkins et al, 2001;Hayes et al, 2015;Marcell et al, 2003;Marcell et al, 2014;Pollock et al, 2015;Proctor and Joyner, 1997;Sanada et al, 2009;Tarpenning et al, 2004b;Trappe et al, 2013; Yataco et al,…”
Section: Fat-free Massmentioning
confidence: 99%
“…Only three studies (DubÉ et al, 2016;Schmidt et al, 2015;Yataco et al, 1997) reported measures of whole-body fat mass (FM) measured using DXA or hydrostatic weighing. Three study groups included master endurance athletes (14.1 ± 3.6 kg FM, n=91), 2 study groups included older untrained individuals (20.1 ± 6.3 kg FM, n=65) and 1 study group included young endurance trained individuals (12.0 ± 4.2 kg FM, n=14).…”
Section: Fat Massmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Wroblewski et al (2011) showed that despite an increase in total body fat percentage with age, mid-thigh muscle area, quadriceps area, and specific strength did not decline significantly with age in master athletes. Dubé et al (2016) recently showed that lifelong exercise was associated with higher intramyocellular triglyceride and glycogen content in all muscle fibers and higher metabolic efficiency during exercise. From a neuromuscular viewpoint, Power et al (2010) also showed master runners preserved the number of functioning motor units in the tibialis anterior well into the seventh decade of life providing evidence that chronic activity has beneficial effects not only on the muscle fibers but also on the motoneuron.…”
Section: Age-related Changes In Physiological Determinants Of Enduranmentioning
confidence: 99%